TRIGATRA PERNIKAHAN KRISTEN: ELABORASI YURIDIS, SOSIOLOGIS, DAN HUMANISTIS - Paulus Dimas Prabowo (SEKOLAH TINGGI TEOLOGI INJILI SETIA SIAU, 2022)
This article is a response to the condition of marriage in Indonesia in the last five years, where there has been a significant increase in the divorce rate. The author feels compelled to present the concept of Christian marriage comprehensively covering the juridical, sociological, and humanistic aspects so that people's domestic life is well maintained and lovingly until death do them part. The method used is literature study using secondary sources including books and articles discussing Christian marriage, and new discoveries according to related aspects. The results showed that the concept of Christian marriage can be seen from three categories, namely juridical, sociological, and humanistic. The juridical aspect is related to divine provisions where God's will for marriage is monogamous, indivisible, procreative, and heterosexual. The sociological aspect is related to the intersection of Christian marriage with the public, where marriage needs to be recognized by the community and has a positive influence on society. The humanist aspect is related to humans which includes psychological and sexual dimensions, because humans are created to have an integrated physical and mental aspect.